Tahap pengkomersilan produk elektrik bercirikan teknologi hijau di Malaysia: Kajian kes kawasan Bandaraya Kuala Lumpur - Ismail, Hamidi; Samuri, Hamim; Ishak, Mohamed Mustafa (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Commercialization level of green-tech electrical products among urban communities in several parts of the world is still low.This study sought to to assess the level of commercialization in the community area of Kuala Lumpur City.Primary data were gathered from a survey via electronic mails involving with 391 residents of Kuala Lumpur City area and the main analytical technique used was descriptive statistics. The findings revealed that the commercialization level of green-tech electrical products was at a moderate level of 59.8 percent (the combined results of the Likert Scale 4 and 5) with a mean value of 3.61. This was in contrast to the conventional observation asserting that the commercialization was still low. The implication of the study is the need for further improvements of the existing National Green Technology Policy in the context of marketing stimulation and incentives for the policy is still seen as failing to state the real direction for the national commercialization of green-tech electrical products.